Comparative Analysis of Strategies for Innovative Development of The Economy: The Experience of The EU Countries. - Verbivska, Liudmyla (Quality - Access to Success, 2022)
The relevance of the study. Innovative development of the EU countries provided additional incentives in the framework of the integration association, as all 27 countries are involved in the innovation process. The article examines the indicators of innovative development of the EU states. The authors rely on materials demonstrating that innovation leaders and strong leaders are in the European innovation ranking, at a high level of innovation convergence, as innovation within the EU is actively funded through the TEMPUS/TACIS and Horizon 2020 programs. The practical significance of studying Cluster analysis allows us to study the real position and nature of innovative connections of EU countries in the dynamics, by establishing the closeness of the connection within the cluster and the characteristic differences between clusters. The purpose of this study The purpose of the study is to examine changes in the position of innovation links of EU countries on the main indicators of the Global Innovation Index. The method of research. The article uses the method of cluster analysis to process statistical information. Research results. Our study showed that the countries on the level of innovation development are united into 3 clusters because due to the progressive development in the implementation of innovation strategies, the policy of convergence gives certain positive results. Conclusions of the study. The obtained results of the research of innovation relations of EU countries based on indicators of the Global Innovation Index showed how a number of EU countries have improved their positions in comparison with the assessment of the European Innovation Scoreboard, in which countries are grouped into 4 clusters. The analysis carried out in the article showed that Estonia's position has significantly improved. In the implementation of innovation strategies, EU countries have achieved a reduction in the innovation gap through the development of joint projects and programs and the convergence of innovation links. As a result, the positions of many EU countries have improved and it is reasonable to combine them into 3 clusters: innovative leaders, innovative followers, and innovative outsiders.
Verbivska LIUDMYLA, Tkachuk SVITLANA, Mashtaler OLHA, Rysin MARIIA, Trynchuk VIKTOR. Comparative Analysis of Strategies for Innovative Development of The Economy: The Experience of The EU Countries. Quality - Access to Success, 2022, 23 (189), pp. 184–191
Keywords: innovation development, innovation gap, innovation strategies